KETELADANAN GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SEBAGAI STRATEGI PENGUATAN KARAKTER SISWA SEKOLAH MENENGAH PERTAMA - Dede Kurniawan; Randika Randika; Fajar Apriliandi; Muhamad Hasyim As'ari; Pemas Endriansyah; Hadi Wiryanto (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2025)
Teacher role modeling plays a strategic role in shaping students’ character, particularly in Civic Education (Pendidikan Pancasila dan Kewarganegaraan/PPKn) which aims to instill moral, ethical, and national values. This study aims to analyze the role of PPKn teacher role modeling as a strategy for strengthening students’ character in junior high schools. The research employed a qualitative approach with a case study method. The subjects consisted of PPKn teachers, students, and school principals, while data were collected through observation, in-depth interviews, and documentation. The results showed that PPKn teacher role modeling, as reflected in discipline, responsibility, integrity, and social care, significantly influenced the strengthening of students’ character. This role modeling was evident not only during the learning process but also in social interactions within the school environment. The study concludes that PPKn teachers who consistently serve as role models can be an effective strategy in shaping students’ character based on Pancasila values. The implications of this study highlight the need for continuous training and development programs for teachers to strengthen their role modeling as an integral part of character education in schools.